Kontribusi penerimaan pajak bumi dan bangunan perdesaan dan perkotaan terhadap pendapatan asli daerah Kabupaten Bandung Barat tahun 2014-2021 - Kurniawan, Reza; Setiajatnika, Eka (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine how much influence the Rural and Urban Land and Building Tax has on the Regional Original Income of Kabupaten Bandung Barat. The method used in this study is a quantitative method with a descriptive approach. The data used is secondary data in the Kabupaten Bandung Barat Regional Original Revenue report. The results of the study show that the Rural and Urban Land and Building Taxes have a significant effect on Regional Original Income.